On the Nonlinear Theory of Micropolar Bodies with Voids - Marin Marin (Journal of Applied Mathematics)
This paper is concerned with the nonlinear theory of micropolar, porous, and elastic solids. By using the theory of Langenbach, within this context, we obtain some existence and uniqueness results.